THE EFFECTS OF SOCIAL MEDIA MARKETING FUNCTIONALITIES ON CONSUMER DECISION-MAKING: THE MODERATING ROLE OF TRUST AND EMOTIONAL INTELLIGENCE - May, Amy Yeo Chu; Hong, Ling Wei; Tiong, Jeffton Low Boon (Graduate Program of Universitas Tarumanagara, 2023)
The study aims to expand the knowledge on how functionalities of social media and the social influence could boost the social media marketing efforts, which may assist the social media marketers and users to explore a specific aspect of the user experiences as well as its implications for the business companies. It provides an understanding on how the emotional intelligence could affect the people in Malaysia, particularly in the relationship between the social media marketing and the consumer decision-making processes. The data amassed was based on 260 respondents and then analysed using Statistical Package for the Social Sciences (SPSS) and the Structural Equation Modelling (PLS-SEM). The findings reveal that the social media marketing that includes identity functionality, information sharing functionality, conversation functionality and social influence are found to be the predictors in consumer decision-making. People with the higher self-awareness, would enhance the relationship between the social media marketing and the consumer decision-making. Equally important is the interplay trust manifests on the consumer decision-making and social media marketing. Hence, marketers can gain insights on how to find new opportunities specifically focusing on the four dimensions of social media marketing which determine how potential consumers make decision during the unprecedented COVID-19 challenging era.